PENGGUNAAN "PARTIAL ADJUSTMENT MODEL" SEBAGAI ALTERNATIF ALAT ANALISIS DAYA SAING KOMODITAS PERTANIAN DALAM PERDAGANGAN INTERNASIONAL - HENDAYANA, RACHMAT (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005)
There are some tools for competitive advances analysis in international trade commodity that one is “Partial Adjustment Model” (PAM). The PAM methods can be estimate through linier regression or logarithm, while competitive advantage parameter shown by elasticity coefficient. The PAM methods applying in pepper trade using Pepper Statistical Years Book for more years from International Pepper Community (IPC), shows that Indonesian pepper export share is equal with Malaysia. There is show increase. Elasticity coefficient for market share to pepper price in the world is relatively small than Malaysia both in short term as well as long term i.e. about 0.07 and 0.013 respectively. This condition show that world pepper price exchange for pepper Indonesian export is not elastic.
Keywords: Partial Adjustment Model, Pepper, Competitive Advantages, International Trade, IPC.